2017
DOI: 10.5858/arpa.2016-0461-oa
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Transfusion-Transmitted Cytomegalovirus and Cytomegalovirus Disease Mitigation

Abstract: Context.— Cytomegalovirus (CMV) can be transmitted by cellular blood products, leading to severe disease in immunosuppressed patients such as neonates and transplant recipients. To mitigate transfusion-transmitted CMV (TT-CMV), “CMV-safe” blood products (leukoreduced and/or CMV-seronegative) are transfused. Attempts to develop practice guidelines for TT-CMV mitigation have been limited by paucity of high-quality clinical trials. Objective.— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the United States, a 2017 survey reported 90% of responding institutions use leukoreduction as the primary TT-CMV prevention strategy; 40% of respondents indicated that seronegative blood use was by physician discretion in the absence of clinical guidelines. 27 Given the TT-CMV observations in our study and those in HSCT populations, [19][20][21][22][23] discontinuation of use of seronegative blood products for SOT recipients provides an evidence-based opportunity for transfusion cost reduction in settings where leukoreduced blood products are already being given. This may be further justified when the risk of TT-CMV is compared to the high incidence of donor-derived CMV and CMV reactivation when donors or recipients are seropositive; the latter risks are considered acceptable when managed using antiviral drugs and laboratory surveillance strategies.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the United States, a 2017 survey reported 90% of responding institutions use leukoreduction as the primary TT-CMV prevention strategy; 40% of respondents indicated that seronegative blood use was by physician discretion in the absence of clinical guidelines. 27 Given the TT-CMV observations in our study and those in HSCT populations, [19][20][21][22][23] discontinuation of use of seronegative blood products for SOT recipients provides an evidence-based opportunity for transfusion cost reduction in settings where leukoreduced blood products are already being given. This may be further justified when the risk of TT-CMV is compared to the high incidence of donor-derived CMV and CMV reactivation when donors or recipients are seropositive; the latter risks are considered acceptable when managed using antiviral drugs and laboratory surveillance strategies.…”
Section: Discussionmentioning
confidence: 71%
“…After reviewing data from this study along with other available evidence, 26 a decision was made in Canada to no longer perform additional screening for seronegative blood except to maintain an inventory for rare intrauterine transfusion. In the United States, a 2017 survey reported 90% of responding institutions use leukoreduction as the primary TT‐CMV prevention strategy; 40% of respondents indicated that seronegative blood use was by physician discretion in the absence of clinical guidelines 27 . Given the TT‐CMV observations in our study and those in HSCT populations, 19‐23 discontinuation of use of seronegative blood products for SOT recipients provides an evidence‐based opportunity for transfusion cost reduction in settings where leukoreduced blood products are already being given.…”
Section: Discussionmentioning
confidence: 99%
“…11 A recent large, national survey demonstrated 90% of institutions (2,712/3,032) use universal leukoreduction. 12 This widely employed and effective prevention strategy has likely helped reduce FNHTRs nationwide, so there are now fewer to prevent. 12 Irradiation is another common modification of blood components used to prevent transfusion-associated graft-vshost-disease (TA-GVHD) for recipients with significantly compromised cellular immunity.…”
Section: What You Should Do Insteadmentioning
confidence: 99%
“…12 This widely employed and effective prevention strategy has likely helped reduce FNHTRs nationwide, so there are now fewer to prevent. 12 Irradiation is another common modification of blood components used to prevent transfusion-associated graft-vshost-disease (TA-GVHD) for recipients with significantly compromised cellular immunity. TA-GVHD is a rare but nearly universally fatal delayed complication of transfusion.…”
Section: What You Should Do Insteadmentioning
confidence: 99%
“…A recent systematic review and meta-analysis estimated a global HCMV seroprevalence of 83% in the general population, 86% in women of reproductive age, and 86% in donors of organs or blood [3]. HCMV can be transmitted through motherto-child transmission; horizontal transmission; hospital-acquired respiratory, neurological, blood, and digestive system diseases; and other multi-system diseases, resulting in fetal malformation, birth defects [4], or poor prognosis of transplant patients with low immunity [5][6][7][8]. Following the establishment of infection, HCMV is usually latent (with only a few virus particles being released outside the cell), and the infected persons remain asymptomatic and become lifelong infectious carriers [9].…”
Section: Introductionmentioning
confidence: 99%